ABDOMINAL COMPARTMENT SYNDROME AMONG CRITICALLY ILL SURGICAL AND TRAUMATISED PATIENTS: EXPERIENCE AT PIMS, ISLAMABAD - Saaiq, Muhammad; Shah, Syed Aslam; Khaliq, Tanwir (Journal of Ayub Medical College Abbottabad, 2009)
Background: Raised intra-abdominal pressure (IAP) accompanied by evidence of organ dysfunction constitutes abdominal compartment syndrome (ACS). The ACS is now becoming an increasingly recognised fatal entity in the critically ill surgical and traumatized patients receiving critical care. The objectives were to determine the frequency of abdominal compartment syndrome (ACS) in critically ill surgical and traumatised patients and to identify the risk factors associated with its development in our patients. Methods: This descriptive study was conducted at Department of Surgery, Pakistan Institute of Medical Sciences (PIMS), Islamabad from July 2004 to February 2005. Two hundred critically ill adult surgical and traumatised patients who needed catheterisation were included in the study. Patients who had cardiac tamponade, tension pneumothorax, status asthmaticus, bladder outflow obstruction, pre-existing end organ failure and those not consenting to participate in the study were excluded. Diagnosis of the underlying surgical condition was made by history, physical examination and necessary investigations. The main diagnostic tool employed for detecting ACS was the measurement of intra-cystic pressure (ICP) which was taken as an indirect measure of intra-abdominal pressure (IAP). It was measured four hourly by employing simple fluid column manometry method. Blood pressure, pulse rate, temperature, respiratory rate and urine output were recorded 4 hourly. Arterial blood gases (ABGs) and renal function tests (RFTs) were performed daily. ACS was diagnosed on the basis of raised IAP of >10 mmHg coupled with evidence of one or more end organ failure. A variety of risk factors that lead to ACS were studied among the patients. Results: Out of 200 patients, six had ACS. The overall frequency was thus 3%. The M:F was 2:1. Most of the patients were in the age range of 31-40 years. Severe peritonitis, severe gut oedema, SIRS and tense ascites were recognised as statistically significant risk factors for the development of ACS. All patients with ACS had features of multiorgan dysfunction. There was 80% in-hospital mortality among the ACS sufferers. Conclusion: ACS develops in a significant number of critically ill and traumatised patients developing quickly and proving fatal without ACS specific interventions. All such high risk patients should undergo serial ICP measurements as a screening test for early detection of ACS. Keywords: Abdominal compartment syndrome, ACS, Intra-abdominal pressure, Intra-cystic pressure